A Heuristic algorithm for robustly stable generalized disturbance observer synthesis with closed loop consideration. (July 2019) - Xiang, Guofei; Su, Jianbo
Abstract: This paper investigate the problem of disturbance observer (DOB) based disturbance rejection control with closed loop performance guaranteed. A generalized DOB based control framework is presented. Specifically, the novel DOB framework if obtained by taking advantage of Youla factorization of a two degree-of-freedom controller in a nontraditional way. Closed loop analysis clarifies that generalized DOB inherits advantages of the traditional one, while mitigating its restrictions. Through appropriate reconfiguration, the Q-filter synthesizing is transformed into reduced-order controller designing. By taking advantage of the Kalman–Yakubovich–Popov (KYP) lemma and projection lemma, a two-stage heuristic algorithm is proposed: an initial full information controller is firstly established for the reconfigured system, which is used to heuristically obtain the reduced-order controller by alternately solving LMIs in the second stage. Finally, we illustrate the application of these results to minimum phase and non-minimum phase plants. Elaborated comparisons between the two-stage heuristic algorithm based generalized DOB and the state-of-art H ∞ based DOB are conducted, the results verify the effectiveness and advantages. Highlights: The limitations and difficulties of conventional DOB has been analyzed when applying it to practical problems. A novel disturbance observer architecture, generalized DOB, is proposed by taking advantage of Youla parametrization. Its disturbance rejection abilities and potential performance advantages of generalized DOB has been investigated in detail. A heuristic two-stage parameter optimization algorithm has been proposed with the help of Kalman–Yakubovich–Popov (KYP) lemma.